2018
DOI: 10.1134/s0032945218030013
|View full text |Cite
|
Sign up to set email alerts
|

First Record of African Angel Shark, Squatina africana (Chondricthyes: Squatinidae) in Indian Waters, Confirmed by DNA Barcoding

Abstract: Abstract-A single specimen of African angel shark, Squatina africana (Regan, 1908) was caught off Lakshadweep (11°5′47″ N; 72°2′21″ E), India in September 2016. The present study is a new report of the above species from Indian waters. In addition to classical methodologies, DNA barcoding was also adopted for species identification. The 650 bp-long region of mitochondrial Cytochrome Oxidase subunit I was sequenced to obtain the DNA barcode for the species under study. The sequence divergence value within spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…All species delimitations split S. africana into four MOTUs. A recent study which included sequences from South Africa and Indian Ocean specimens, found a high number of haplotypes within S. africana [73] using DNA fragments of COI gene, and with a high K2-P genetic distances (up to 2.5%), when compared with values reported in this study between other pairs of nominal Squatina species (e.g., 0.99% between specimens of S. albipunctata and S. pseudocellata). Similar to S. californica, the split of S. africana into 4 MOTUs may be explained due to the life-traits of angel sharks and the geographical barriers.…”
Section: Discussioncontrasting
confidence: 44%
“…All species delimitations split S. africana into four MOTUs. A recent study which included sequences from South Africa and Indian Ocean specimens, found a high number of haplotypes within S. africana [73] using DNA fragments of COI gene, and with a high K2-P genetic distances (up to 2.5%), when compared with values reported in this study between other pairs of nominal Squatina species (e.g., 0.99% between specimens of S. albipunctata and S. pseudocellata). Similar to S. californica, the split of S. africana into 4 MOTUs may be explained due to the life-traits of angel sharks and the geographical barriers.…”
Section: Discussioncontrasting
confidence: 44%
“…However, despite the interdependence of both disciplines, their synergic and harmonic application has not been as frequent as needed. Recent taxonomic studies on angel sharks (Vaz & de Carvalho 2013 and other successful examples of combining taxonomy and genetics (Ambily et al 2018), with this updated morphological characterization of the Chilean angel shark, questions on geographic range, estimations of abundance, and real incidence in landings can be clarified to ultimately inform better conservation practices of this critically endangered species (Dulvy et al 2020) and other angel sharks on the Pacific coast of America.…”
Section: Conservationmentioning
confidence: 99%
“…Recent efforts in identifying and describing angel sharks have adopted a more integrative approach by combining morphology with other disciplines, such as genetics (Padial et al 2010;Long et al 2021). For example, the identification of the African angel shark Squatina africana Regan, 1908 was improved by combining morphology and DNA-barcoding, enabling a better delimitation of its distribution range which was expanded into the southwestern Indian Ocean (Ambily et al 2018). In addition, genetic data have been successfully used in identifying angel sharks and in constructing phylogenies (e.g., Stelbrink et al 2010;Vélez-Zuazo & Agnarsson 2011;Naylor et al 2012;López-Romero et al 2020), which has been particularly useful when studying co-occurring species.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 illustrates the numerical model and mesh configurations utilized in the analysis. While the cylindrical unit cell model can be conceptualized as a 3D model with the vertical axis passing through the column center, geometric constraints in PLAXIS necessitated the adoption of a square unit cell equivalent, as utilized in earlier studies (Ambily;Gandhi, 2007;Samadhiya, 2016a). Consequently, a square unit cell model was employed in this study.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Several researchers have investigated the behavior of Sand-Fiber Mix (SFM) or geogrids using both numerical and experimental methods. For instance, comprehensive parametric studies involving random fibers have been conducted to analyze the behavior of SFM and assess the impact of factors such as fiber length, depth, and quantity on the bearing capacity of sand piles (Ambily;Gandhi, 2007;Shooshpasha, 2017;Malarvizhi;Ilamparuthi, 2008;Murugesan;Rajagopal, 2010).…”
Section: Introductionmentioning
confidence: 99%